Plan de marketing para el restaurante Doña Yoli de la ciudad de Sucùa, cantón Sucùa, provincia de Morona Santiago para el año 2017. - Siguenza Cárdenas, Diana Angélica (2018)
Doña Yoli restaurant is a micro-enterprise that contributes to the economy of the Sucúa canton, its main activity is the sale of food and drinks, always trying to offer the best quality to its customers; However, the necessary studies have not been carried out in order to sufficiently understand the environment and thus take decisions and strategic actions that allow the company to have a greater market share. In such virtue the application of a Marketing Plan in the restaurant Doña Yoli, will allow to have a broader vision of the future, since it will facilitate the steps to reach the proposed goals, based on the internal and external analysis of the company. In this way, for the development of this research, the general objective is met: designing a marketing plan for the restaurant "Doña Yoli" of the Cantón Sucúa. From this objective, specific objectives are derived, which allow the development of this investigation, these have to do with the diagnosis, execution and control. In order to comply with the pre-named objectives, different methods and techniques were used, among the first ones the methods can be noted: deductive, inductive, historical, analytical, statistical and descriptive. Within the techniques, the interview was applied, which was done to the Company Manager and the survey applied to 200 clients and 8 to the employees of the company DOÑA YOLI In this context, important information was obtained, which served to make the situational diagnosis of the company, both externally and internally. With the external diagnosis the MEFE matrix was structured, which includes the opportunities and threats, after carrying out the rating and weighting, a value of 2.60 points is obtained, which means that there is a predominance of opportunities over the threats; while the MEFI matrix, composed of strengths and threats, yields a weighted value of 2.32 points, which means that there is a predominance of weaknesses over strengths. Subsequent to the aforementioned, the SWOT matrix is established, from which the high impact matrix is derived, which made it possible to determine the FO, FA, DO and DA strategies, as well as defining the strategic objectives, which lead to the formulation of the marketing. It should be noted that the implementation of this marketing proposal has a cost of $ 10,467; same that will be financed by the same company. Finally, the conclusions and recommendations are presented, where the manager of the company "DOÑA YOLI" is presented the importance of the implementation of the Marketing Plan, since this will allow it to position itself in the minds of consumers and subsequently achieve its loyalty. In such a way that sales and profits of the company will increase. In addition, we recommend strict monitoring of compliance with the objectives set, as well as analyzing periodically their effectiveness in increasing the market share of the company. To be able to generate a competitive advantage, through a better presentation of menus, that are attractive and appealing to customers